Peptide Receptor Radionuclide Therapy and Primary Brain Tumors: An Overview - Andrea Cimini; Maria Ricci; Francesca Russo; Martina Egidi; Ferdinando Calabria; Antonio Bagnato; Orazio Schillaci; Agostino Chiaravalloti (MDPI AG, 2021)
Primary brain tumors (PBTs) are some of the most difficult types of cancer to treat, and despite advancements in surgery, chemotherapy and radiotherapy, new strategies for the treatment of PBTs are needed, especially for those with poor prognosis such as inoperable/difficult-to-reach lesions or relapsing disease. In regard to the last point, malignant primary brain tumors remain some of the most lethal types of cancer. Nuclear medicine may provide exciting new weapons and significant contributions in the treatment of PBTs. In this review, we performed literature research in order to highlight the possible role of peptide receptor radionuclide therapy (PRRT) in the treatment of PBTs with radiolabeled molecules that bind with high-affinity transmembrane receptors such as somatostatin receptors (SSTRs), neurokinin type-1 receptor and prostate-specific membrane antigen (PSMA). These receptors are overexpressed in some cancer types such as gliomas, meningiomas, pituitary tumors and medulloblastomas. A comprehensive overview of possible applications in this field will be shown, providing knowledge about benefits, feasibility, developments and limitations of PRRT in this type of tumor, also revealing new advantages in the management of the disease.